The Impact of Kidnapping for Ransom on Nigeria’s Image - Osegboun, Adebola Esther; Oladipo, Temidayo David (African Journal of Stability and Development (AJSD), 2023)
Kidnapping is a long-standing global phenomenon, which is not unique to any continent or country. However, it has taken on a new dimension in the 21st century with the development of kidnapping for ransom. Kidnapping for ransom is now a lucrative business in many nations of the world, and has grown particularly worrisome in Nigeria, due to the country’s weak security system. It is in this regard that this article examines the impact of kidnapping for ransom on Nigeria’s image. The study explores the evolution of kidnapping in Nigeria, causes of kidnapping, effects of kidnapping on victims and its impact on Nigeria’s image. The study, which is qualitative in nature, discovers that Nigeria- a country that has long struggled with maintaining a positive image has allowed kidnapping to linger for too long. The paper posits that Nigeria has become insecure for both locals and foreigners and this has consequently affected foreign direct investment, tourism and migration. The paper thus argues that if kidnapping for ransom is not adequately tackled, it will hinder the growth of the economy arising from the consequence of hampered image of the country in the comity of nations. It therefore concludes that there is a need for the government to take proactive measures rather than reactive ones towards this menace.